Youth Employment Trends and Prospects in the European Union: A Comparative Analysis - Visockaitė, Asta; Urmanavičienė, Audronė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Youth employment is of great importance and relevance nowadays. The article analyses the issues of youth employment among the Member states of the European Union. According to the statistics and research data provided by the World Bank and Eurostat the situation of youth employment among the European Union member states and all across the Globe is deteriorating. The article focuses on analysing the programmes and initiatives of the European Union competent institutions and Member states of the European Union which aim to decrease the rates of youth unemployment.Aim of the study: to evaluate the programs and initiatives aiming to decrease youth unemployment which are currently being implemented by the Institutions and Member states of the European Union.Methods of the study: secondary analysis of the collected data (general overview). Results: programs and measures aiming to decrease the youth unemployment rates in the EU Member states are being vastly initiated and implemented since early 2010. With the endorsement of the Plan to tackle and reduce youth unemployment rates, which foresees to accelerate the implementation of the Youth Employment and the Youth Guarantee initiatives, various youth employment promotional tools are being applied among the Member states. After analyzing and evaluating the aforementioned programs and initiatives carried out by the Institutions and Member states of the European Union, general tendencies of decreasing the youth unemployment rates may be determined.